2018
DOI: 10.1007/978-3-030-06016-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Converting Alzheimer’s Disease Map into a Heavyweight Ontology: A Formal Network to Integrate Data

Abstract: Alzheimer's disease (AD) pathophysiology is still imperfectly understood and current paradigms have not led to curative outcome. Omics technologies offer great promises for improving our understanding and generating new hypotheses. However, integration and interpretation of such data pose major challenges, calling for adequate knowledge models. AlzPathway is a disease map that gives a detailed and broad account of AD pathophysiology. However, AlzPathway lacks formalism, which can lead to ambiguity and misinter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Efforts to interpret sequence data obtained from the brains of patients are underway, and newer methods and hypotheses have been proposed to understand the pathogenesis of neurological diseases (Bizzotto & Walsh, 2022;Exposito-Alonso & Rico, 2022;Henry et al, 2021;Vilela et al, 2022;Wilfert et al, 2017).…”
Section: Variation In the Neuronal Genome Contributes To Neurological...mentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts to interpret sequence data obtained from the brains of patients are underway, and newer methods and hypotheses have been proposed to understand the pathogenesis of neurological diseases (Bizzotto & Walsh, 2022;Exposito-Alonso & Rico, 2022;Henry et al, 2021;Vilela et al, 2022;Wilfert et al, 2017).…”
Section: Variation In the Neuronal Genome Contributes To Neurological...mentioning
confidence: 99%
“…A report showed that DNMs distribute unevenly in several to 100 kilobases in neurons of autistic brains, suggesting examination of genome‐wide characteristics in neurons may give us hints in information regarding a variable genome in neurodevelopmental disorders (Michaelson et al, 2012). Efforts to interpret sequence data obtained from the brains of patients are underway, and newer methods and hypotheses have been proposed to understand the pathogenesis of neurological diseases (Bizzotto & Walsh, 2022; Exposito‐Alonso & Rico, 2022; Henry et al, 2021; Vilela et al, 2022; Wilfert et al, 2017).…”
Section: Variation In the Neuronal Genome Contributes To Neurological...mentioning
confidence: 99%
“…The study begins by examining the taxonomic process using the taxonomic levels in [30,31]. This is an ordering system that allows a set of elements to be grouped within certain predefined categories.…”
Section: Taxonomymentioning
confidence: 99%
“…ADO has been designed to be useful for ontology-driven searching of the literature. In [31], the AD Map Ontology (ADMO) is proposed, in order to describe knowledge about AD related biological pathways, based on systems biology terms. In [32], ontologies related to the area of neurodegenerative disease are presented, but the authors claim that all these ontologies have not be maintained over the time.…”
Section: Ad Data Collections and Ontologies: A Way For Data Harmoniza...mentioning
confidence: 99%